(3HjGf NWC CHj YHO Gddg eMeO Hf ESeGYjd GdHNGQi aj JGQjNgs - (3YHO GdQMef Hf eMeO CHj MGJe GHf EOQjS Hf GdefPQ GdJejej GdMfXdqj GdQGRqj, CHh eMeO , GHf nCHj MGpJe , J (B327 (3g`s; (3CHh YHO Gddg eMeO Hf ESeGYjd Hf EHQGgje GdLYaj GdHNGQj, GdEeGe GdHNGQj,J (B256 (3g` s ((3CHh HcQ Hf Ydi Hf CSeGYjd GdHgfSi GdCfUGQi GdTGaYi s)
(3ChdgG (B:s
(3bGd CHh eMeO SeYJ CHj jbhd bGd ChRQYI s
(3BNQgG (B:s
(3gPG eG GNQL ef HjGf NWC eMeO Hf GSeGYjd ai JGQjNg Yf CHj RQYI hCHi MGJe QVi Gddg Yfge CLeYjf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B119 - (3U(B143s
(3JcQQ CjVkG JMJ Qbe (B" 595" (3JGQjNs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3EUdGMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJGQjNs